Racial/Ethnic Disparities in Length of Life after Dementia Diagnosis: an 18-Year Follow-up Study of Medicare Beneficiaries - Yi Chen; Eileen Crimmins; Patricia Ferido; Julie M. Zissimopoulos (Elsevier, 2022)
Summary: Background: This study quantifies survival time after dementia diagnosis and assesses mechanisms driving differences across race/ethnicity to inform care and financial planning. Methods: Using 100% Medicare claims data, we identified 670,955 beneficiaries with incident dementia diagnosis in 2001 and followed them through 2018. We quantified racial/ethnic differences in post-diagnosis survival and for subgroups defined by sex, age at diagnosis, socio-economic status, and geography. Additionally, we investigated racial/ethnic time trends in 5-year mortality risk of 8,080,098 beneficiaries with incident dementia in years 2001-2013. Findings: Hispanics and Asians diagnosed with dementia had 40% lower mortality risk and African Americans had 13% lower mortality risk than Whites. There was no difference between American Indians/Alaska Natives and Whites. Racial/ethnic differences were of similar size in sex, age at diagnosis, and urban/rural subgroups; however, the survival advantage between non-Whites and Whites was larger among low-income beneficiaries. State differences in mortality among Blacks were consistent with a Southern divide but not for Asians and Hispanics. The Asian-White and Hispanic-White mortality differences decreased 2001 to 2013. Interpretation: Racial/ethnic survival differences after dementia diagnosis have implications for magnitude of financial impact of dementia on individuals and families. Quantifying survival differences and changes over time informs family, community, and societal level long-term care planning for a large and growing population of persons living with dementia. Variation in the size of racial/ethnic differences by economic status and geographic location provides opportunities for targeted strategies to reduce economic consequences and improve care and quality of life after dementia diagnosis. Funding: National Institutes of Health (R01AG055401, P30AG066589).